2006
DOI: 10.1089/pho.2006.24.10
|View full text |Cite
|
Sign up to set email alerts
|

Polychromatic LED in Oval Full-Thickness Wound Healing in Non-diabetic and Diabetic Rats

Abstract: The effect of polychromatic LED therapy in oval full-thickness wound-healing in the diabetic model with the use of 5 and 10 J/cm(2) is promising. Further studies to determine optimum dosimetry and efficacy of LEDs are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 11 publications
1
18
0
2
Order By: Relevance
“…However, there are no studies in the literature using LED light on wound healing in hypothyroid rats. Several studies, both in vitro and in vivo, have shown that LED phototherapy influences tissue repair [9,[12][13][14][15][16][17] and consists in an alternative for the treatment of both cutaneous and mucosal wounds [15,18], but we do not yet have a full understanding of the mechanisms involved in this process. It seems that the LED light treatment (630-1000nm) stimulates the photoacceptor cytochrome c oxidase and the mitochondrial metabolism, resulting in increased energy metabolism and production of adenosine triphosphate (ATP) by target cells, such as increased collagen synthesis by fibroblasts, accelerating tissue repair [10,11,16,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no studies in the literature using LED light on wound healing in hypothyroid rats. Several studies, both in vitro and in vivo, have shown that LED phototherapy influences tissue repair [9,[12][13][14][15][16][17] and consists in an alternative for the treatment of both cutaneous and mucosal wounds [15,18], but we do not yet have a full understanding of the mechanisms involved in this process. It seems that the LED light treatment (630-1000nm) stimulates the photoacceptor cytochrome c oxidase and the mitochondrial metabolism, resulting in increased energy metabolism and production of adenosine triphosphate (ATP) by target cells, such as increased collagen synthesis by fibroblasts, accelerating tissue repair [10,11,16,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…One potential candidate is the light-emitting diode (LED) light source which has the advantages of portability, high luminance, a relatively narrow spectrum, long lifespan, and low cost. In fact, LEDs in the visible spectrum have been applied to phototherapy in several other skin diseases such as wound healing, 21 acne, 22 and photodynamic therapy. 23 In this study, we tested the efficacy of UV-A1 LEDs in treating hypertrophic scar on rabbit ear.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] However, we do not yet have a full understanding of the mechanisms involved in this.…”
Section: Introductionmentioning
confidence: 99%
“…17 It seems possible that LEDPT presents beneficial effects similar to the ones observed when LPT is used, as several reports on the benefits of the use of LEDs operating at several wavelengths, both in vitro and in vivo, in both normal and pathologic conditions, have been published elsewhere. 2,3,6,[18][19][20][21][22][23][24][25] It is also possible that the mechanism involved is similar.…”
Section: Introductionmentioning
confidence: 99%